Some Remarks on Results Related to ∇-Convex Function - Asif Raza Khan; Faraz Mehmood; Faisal Nawaz; Aamna Nazir (Institute for Research and Community Services (LPPM) ITB, 2021)
In the present article, we give new techniques for proving general identities of the Popoviciu type for discrete cases of sums for two dimensions using higher-order ∇-divided difference. Also, integral cases are deduced by different methods for differentiable functions of higher-order for two variables. These identities are a generalization of various previously established results. An application for the mean value theorem is also presented.